GEMINI output used to develop volumetric reconstruction technique for EISCAT 3D ... - Reistad, Jone Peter; Zettergren, Matthew (Zenodo, 2024)
This dataset is used as a "ground truth" for investigating the performance of a volumetric reconstruction technique of electric current densities, intended to be applied to the EISCAT 3D radar system. The technique is outlined in a mnuscript in preparation, to be referred to here once submitted. The volumetric reconstruction code can be found here: https://github.com/jpreistad/e3dsecs This dataset contain four files: 1) Dataset file 'gemini_dataset.nc'. This is a dump from the end of a GEMINI model run driven with a pair of up/down FAC above the region around the EISCAT 3D facility. Detailes of the GEMINI model can be found here: https://doi.org/10.5281/zenodo.3528915 . This is a NETCDF file, intended to be opened with xarray in python: import xaray dataset = xarray.open_dataset('gemini_dataset.nc') 2) Grid file 'gemini_grid.h5'. This file is needed to get information about the grid that the values from GEMINI are represented in. The E3DSECS library (https://github.com/jpreistad/e3dsecs) has the necessary ...